POLITIK HUKUM PIDANA TERHADAP TINDAKAN TRANSPLANTASI ORGAN TUBUH - Bunga, Dewi (Fakultas Hukum Universitas Mahasaraswati Denpasar, 2017)
Organ transplantation is a medical procedure that has been done since the 20th century to improve the quality of life of patients. The demand for organs more than the supply of donor organs. Patients also had to wait to get the desired organ. This condition is used to conduct illegal organ trade (organ trafficking).Organ trafficking can be made online. Indonesia legalize organ transplants, but prohibits all forms of organ trafficking. Criminal law policy against acts of organ trafficking in Indonesia is regulated in the Act Number 36 of 2009 on Health. Transplants can only be done for humanitarian purposes and is done by health workers who have the expertise and authority to do so and do in a particular health care facility.